Survei Dan Minat Wisatawan Berkunjung Ke Salah Satu Potensi Wisata Olahraga Di Yogyakarta - Kurniawati, Indri; Sumariyanti, Sumariyanti; Guntur, Guntur (JURNAL DESTINASI PARIWISATA, 2023)
The development tourism, is not only about refreshing but also activity of sport can be included in tourism. The impact of pandemic covid-19, has influenced the development of sport tourism in Indonesia. Yogyakarta, one of the most tourism destination, has many kinds of sport tourism spot. The reasons which can influence tourist arrival in a destination are tourists’ motivation. This research aims to know the domestic tourist’s motivation in visiting one sport tourism destination called Tankaman Natural Park in Kaliurang, Hargobinangun. This research applies the survey method and descriptive analysis with a quantitative approach. The data is obtained by distributing questionnaires, conducting the interview, and doing direct observation. The sample of this research is the domestic tourists. The research shows the motivation of domestic tourists visit to Tankaman Natural Park are dominantly fantasy motivation that the tourists could escape from their routines to seek comforts and hang out with family. And the second is to get physical activity by doing sport in tourism destination. Keywords: tourist motivation, sport tourism, tourism product